2012
DOI: 10.1111/j.1582-4934.2011.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microdissected neurons by 18O mass spectrometry reveals altered protein expression in Alzheimer's disease

Abstract: It is evident that the symptoms of Alzheimer's disease (AD) are derived from severe neuronal damage, and especially pyramidal neurons in the hippocampus are affected pathologically. Here, we analysed the proteome of hippocampal neurons, isolated from post-mortem brains by laser capture microdissection. By using 18O labelling and mass spectrometry, the relative expression levels of 150 proteins in AD and controls were estimated. Many of the identified proteins are involved in transcription and nucleotide bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Alterations in lectin affinity for proteins involved in, for instance, Glc metabolism (a-enolase, c-enolase, and glutamate dehydrogenase), chaperone functions (Glc-regulated protein 78, heat shock protein 90, protein disulfide isomerase, and Glc-regulated protein 96), cytoskeletal maintenance [GFAP, tropomyosin (TPM)1, TPM2, TPM3, 14-3-3-c,e,f, gelsolin, and calreticulin], synaptic function (dihydropyrimidase 2, Rab GDP dissociation inhibitor XAP4, and b-synuclein) and cell signaling (protein phosphatase-related protein SDS22), and calmodulin) were identified. Similarly, a recent proteomics study on dissected hippocampal neurons revealed alterations in proteins involved in, for instance, tran-scription and nucleotide binding, glycolysis, the heat shock response, microtubule stabilization, axonal transport, and inflammation [98], suggesting overlapping pathways. Proteins that were identified in both the lectin-binding study and the proteomics study include GFAP and 14-3-3e.…”
Section: Glycoproteomics and Admentioning
confidence: 99%
“…Alterations in lectin affinity for proteins involved in, for instance, Glc metabolism (a-enolase, c-enolase, and glutamate dehydrogenase), chaperone functions (Glc-regulated protein 78, heat shock protein 90, protein disulfide isomerase, and Glc-regulated protein 96), cytoskeletal maintenance [GFAP, tropomyosin (TPM)1, TPM2, TPM3, 14-3-3-c,e,f, gelsolin, and calreticulin], synaptic function (dihydropyrimidase 2, Rab GDP dissociation inhibitor XAP4, and b-synuclein) and cell signaling (protein phosphatase-related protein SDS22), and calmodulin) were identified. Similarly, a recent proteomics study on dissected hippocampal neurons revealed alterations in proteins involved in, for instance, tran-scription and nucleotide binding, glycolysis, the heat shock response, microtubule stabilization, axonal transport, and inflammation [98], suggesting overlapping pathways. Proteins that were identified in both the lectin-binding study and the proteomics study include GFAP and 14-3-3e.…”
Section: Glycoproteomics and Admentioning
confidence: 99%
“…Briefly, the frozen dissected cortices were homogenized in 8 M Urea and 400 mM ammonium bicarbonate followed by trypsinization of 50 μg homogenate. For accurate quantification by MS/MS analysis an 18 O‐labeled internal standard made from a pool of the cortices derived from the 8 individuals was used, as 18 O‐isotope labeling is a robust technique for quantitative proteome analysis . The reproducibility and a dynamic range of at least threefold was confirmed by injecting a 1:1 and a 1:3 mixture of sample and 18 O‐labeled internal standard (Fig.…”
Section: List Of Affected Proteins In Cortex Of Appsw X Nep Ko Vs Apmentioning
confidence: 99%
“…With these approaches, intraneuronal Aβ was found to be significantly increased in neurons from AD brains compared to controls (Hashimoto et al, 2010;Hashimoto et al, 2011).…”
Section: Introductionmentioning
confidence: 96%